الوجود والماهية في الفكر الإسلامي دراسة تحليلية نقدية مقارنة - محمد عبدالعاطي عباس (AR-RĀ’IQ, 2024)
The research aims to highlight the originality of Islamic thought and its ability to interact with the product of human thought “in general,” digest it, and build on it in a way that achieves its identity, subjectivity, and independence, and distinguishes it with features not available in others, the most important of which is: “divineness, because it is derived from revelation, clarity, comprehensiveness, moderation, independence”. “And rationality” through a comparative, critical analytical study of a philosophical issue in its core, which is: (Ontology and Quiddity) in Islamic thought, limited to “theology and philosophical thought” because of the importance of this issue on both the theology and philosophical levels. The research problem revolves around answering two main questions: The first question: Is Islamic thought, especially theological and philosophical, nothing but a simulation and imitation of the views of the Greek philosophical schools that entered to the Muslims through translation and other things, or is it the product of Muslims’ thinking about the divine existence and material existence represented by “the universe and human”?! The second question: Is the Islamic mentality, with its religious reference, capable of formulating independent thought free of foreign influences in a way that achieves its identity and subjectivity and enhances its independence or is it a mentality that is incapable of producing independent thought and that its role is limited to mere simulation, imitation, and transmission of the product of the method used is: analysis, comparison, and criticism. The research concluded several results, the most important of which are: - The topic of (Ontology and Quiddity) is one of the most important topics in Islamic thought. This appeared through the interest of both philosophers and theologians, so it was placed among the main topics whether in philosophy or theology. The discussions that took place around it clearly express the extent of the prowess of the Islamic mentality, and its ability to discuss, argue, and express in the most precise terms the most complex scientific issues. It is a mature and comprehending mentality.